Deciphering hematopoietic stem cell development: key signaling pathways and mechanisms - Morino-Koga, Saori; Yokomizo, Tomomasa (Frontiers in Cell and Developmental Biology, 2024)
Most blood cells derive from hematopoietic stem cells (HSCs), originating from endothelial cells. The induction of HSCs from endothelial cells occurs during mid-gestation, and research has revealed multiple steps in this induction process. Hemogenic endothelial cells emerge within the endothelium, transition to hematopoietic cells (pre-HSCs), and subsequently mature into functional HSCs. Reports indicate transcription factors and external signals are involved in these processes. In this review, we discuss the timing and role of these transcription factors and summarize the external signals that have demonstrated efficacy in an in vitro culture. A precise understanding of the signals at each step is expected to advance the development of methods for inducing HSCs from pluripotent stem cells.